COPD prevalence and characteristics among sample of working population - Stoleski, Sasho; Minov, Jordan; Mijakoski, Dragan; Brborović, Hana; Milošević, Milan; Žaja, Roko (Frontiers Media SA, 2025)
Introduction: COPD is a global public health problem, causing a very high rates of morbidity, mortality, and work disability in the last decades worldwide. Objective: To determine the prevalence and characteristics COPD in a random sample of workers form the city of Skopje, and its relation to occupational exposures. Methods: A cross-sectional study was conducted including 1,867 workers (959 males and 908 females) from the city of Skopje. Afterwards, the study subjects were divided into exposed (1.287/68.9%) and unexposed (580/31.1%) groups based on their current job exposure to noxious particles and gasses. All study participants completed a questionnaire and underwent pre-and post-bronchodilator spirometry. Results: COPD prevalence was 3.9% among all workers. COPD prevalence in exposed workers was significantly higher compared to unexposed (4.7% vs. 2.4%). Significant difference was found in exposed workers with exposure duration longer than 20 years as compared to those with shorter duration of exposure (6.0 vs. 3.2%). COPD prevalence in workers who smoked was significantly higher than in non-smoking workers in both exposed (6.0% vs. 3.9%, p = 0.037) and unexposed (3.9% vs. 1.8%, p = 0.000) groups. The difference between workers with COPD in terms of use of solid and liquid bio fossil fuels at home and central heating/electricity is not significant (5.0% vs. 3.6%), both in exposed (5.4% vs. 4.3%), as well as non-exposed workers (3.8% vs. 1.9%). Conclusion: Our findings confirmed the role of occupational exposures in COPD prevalence indicating a need of more effective preventive activities in order to reduce the overall disease burden.
Keywords: COPD; Occupational exposure; noxious particles and gasses; Spirometry; Questionnaire